2010
DOI: 10.2478/s11535-010-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Extract from Conyza canadensis as a modulator of plasma protein oxidation induced by peroxynitrite in vitro

Abstract: Abstract:The antioxidative activity of the extract from Conyza canadensis in plasma treated with peroxynitrite (ONOO -) (0.1 mM) was studied. C. canadensis is known to possess a broad set of pharmacological effects because of content of various antioxidants, antiplatelet and anticoagulant compounds. The aim of our study was to assess if this extract protects plasma proteins against oxidative/nitrative damages induced by ONOO -. The plasma components are continuously exposed to reactive oxygen/nitrogen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The antioxidant activity of Echinacea polysaccharides has been supported by study of Lee et al (2009). Next, the antioxidant effect of polyphenolic-polysaccharide conjugates from Erigeron and other selected medicinal plants was demonstrated by Saluk-Juszczak et al ( 2010a and 2010b ).…”
Section: Discussionmentioning
confidence: 97%
“…The antioxidant activity of Echinacea polysaccharides has been supported by study of Lee et al (2009). Next, the antioxidant effect of polyphenolic-polysaccharide conjugates from Erigeron and other selected medicinal plants was demonstrated by Saluk-Juszczak et al ( 2010a and 2010b ).…”
Section: Discussionmentioning
confidence: 97%
“…The highest concentration of extract decreased twice the level of protein thiols in reduced forms and increased the homocysteine level about 4.5 times. Accordingly, extract possessed antioxidative properties in vitro, protected plasma proteins against toxicity induced by peroxynitrite and had modulating effects on thiol/disulfide redox status [128].The protective effects of the polysaccharide extract from the plant on platelet proteins against nitrative and oxidative damage induced by ONOO − were studied . The extract of the plant distinctly reduced oxidation and nitration of proteins in blood platelets treated with ONOO − (0.1 mM) and O 2 production in these cells.…”
Section: Erigeron Canadensis (Syn Conyza Canadensis)mentioning
confidence: 99%
“…Previous phytochemical studies revealed the presence of different bioactive compounds in those species: Ailanthus altissima (Mill.) Swingle [ 16 ], Ambrosia artemisiifolia L. [ 17 ], Conyza canadensis (L.) Cronquist [ 18 ], Dittrichia viscosa (L.) Greuter [ 19 ], Xanthium strumarium L. [ 20 ], and Erigeron annuus (L.) Pers. [ 21 ].…”
Section: Introductionmentioning
confidence: 99%